Urinary 8-isoprostane levels and occurrence of lung, colorectal, prostate, breast and overall cancer: results from a large, population-based cohort study with 14 years of follow-up - Gao, Xin; Brenner, Hermann; Cuk, Katarina; Anusruti, Ankita; Xuan, Yang; Schöttker, Ben (Free radical biology and medicine, 2018)
Background: Urinary 8‐isoprostane is an established biomarker for lipid peroxidation. However, the association between its pre-diagnostic levels and cancer incidence has rarely been evaluated. Methods: 8793 older adults from the German ESTHER cohort were followed up for cancer incidence by cancer registry data. A directed acyclic graph was utilized to identify potential confounders. Multivariate Cox regression models were applied to estimate hazard ratios (HRs) and 95% confidence intervals (95% CI). Results: During 14-year follow-up, 1540 incident cancer cases, including 207 lung, 196 colorectal, 218 breast and 245 prostate cancer cases were detected. 8-isoprostane concentrations were positively associated with lung cancer, but not with cancer at the other sites. The HR (95% CI) for the association with lung cancer was 1.61 (1.10, 2.34) for comparison of the top with bottom tertile in total population. The association of 8-isoprostane levels with lung cancer persisted after the adjustment for smoking and other potential confounders and was multiplicative to the effect of smoking. However, 8-isoprostane levels did not improve lung cancer prediction when added to a model containing age, sex and smoking. A protective association of increasing 8-isoprostane levels was observed for prostate cancer incidence but this association was only statistically significant among current smokers. Discussion: Our findings suggest that lipid peroxidation is involved in the development of lung cancer. However, high oxidative stress may be a protective factor for prostate cancer, especially among current smokers.
Available online 17 May 2018
Gesehen am 27.06.2018